Review of current developments on high strength pipeline steels - Ehsan Entezari; Jorge Luis Gonzlez-Velzquez; Diego Rivas Lpez; Manuel Alejandro Beltrn Ziga; Jerzy A. Szpunar (Fracture and Structural Integrity)
Nowadays, an increasing number of oil and gas transmission pipes are constructed with high-strength low alloy steels (HSLA; nonetheless, many of these pipelines suffer from different types of hydrogen damage, including hydrogen-induced cracking (HIC). Many studies are being done to investigate the role of key metallurgical and processing factors to limit the negative effects of HIC in HSLA steel pipes.